Experimental investigation of a thermoelectric generator assisted with heat pipe sinks for pickup car exhaust waste heat recovery - Sukarno, Ragil; Indasyach Moreno, Zavi; Rio Budi Syaka, Darwin; Gunawan, Yohanes; Gama Yoga, Nugroho; Fariz Adzani, Rivaldo; Putra Mustafit, Alvian; Kurniawati, Desy (Komunitas Ilmuwan dan Profesional Muslim Indonesia, 2025)
In internal combustion engine vehicles (ICEV), about 40% of the heat is discharged into the environment as waste heat. This study proposed to develop an energy recovery device to utilize exhaust heat as electrical energy using a thermoelectric generator (TEG) assisted with a heat pipe sink. Six TEG units were installed on the stainless-steel heat block in an exhaust pipe where each TEG unit varied with one-stage TEG and two-stage TEG modules. The results showed that the maximum power generated and TEG efficiency of 1.4 W and 1.14% were obtained under 180oC of exhaust pipe temperature, with a two-stage TEG with a heat pipe sink under forced convection. The use of a heat pipe sink and under-forced convection improves the TEG system's performance by increasing the temperature difference between both sides of the TEG module, which impacts the electric power generated. This research provides some practical guidance for increasing the power and efficiency of TEGs by improving heat transfer performance through heat pipes.